The diagnostic value of multiparameter cardiovascular magnetic resonance for early detection of light-chain amyloidosis from hypertrophic cardiomyopathy patients - Yue, Xiuzheng; Yang, Lili; Wang, Rui; Chan, Queenie; Yang, Yanbing; Wu, Xiaohong; Ruan, Xiaowei; Zhang, Zhen; Wei, Yuping; Wang, Fang (Frontiers in Cardiovascular Medicine, 2022)
Background Early-stage amyloidosis of the heart is prone to be underdiagnosed or misdiagnosed, increasing the risk of early heart failure and even death of the patient. To ensure timely intervention for cardiac light-chain amyloidosis (AL CA), it is vital to develop an effective tool for early identification of the disease. Recently, multiparameter cardiovascular magnetic resonance (CMR) has been used as a comprehensive tool to assess myocardial tissue characterization. We aimed to investigate the difference in left ventricular (LV) strain, native T1, extracellular volume (ECV), and late gadolinium enhancement (LGE) between AL CA patients, hypertrophic cardiomyopathy patients (HCM), and healthy control subjects (HA). Moreover, we explored the value of multiparameter CMR for differential diagnosis of the early-stage AL CA patients from HCM patients, who shared similar imaging characteristics under LGE imaging. Methods A total of 38 AL CA patients, 16 HCM patients, and 17 HA people were prospectively recruited. All subjects underwent LGE imaging, Cine images, and T1 mapping on a 3T scanner. The LV LGE pattern was recorded as none, patchy or global. LV strain, native T1, and ECV were measured semi-automatically using dedicated CMR software. According to clinical and biochemical markers, all patients were classified as Mayo stage I/II and Mayo stage IIIa/IIIb. Univariable and multivariable logistic regression models were utilized to identify independent predictors of early-stage AL CA from HCM patients. Receiver operator characteristic (ROC) curve analysis and Youden’s test were done to determine the accuracy of multiparameter CMR in diagnosing Mayo stage I/II AL CA and establish a cut-off value. Results For Mayo stage I/II AL CA patients, the global longitudinal strain (GLS) absolute value (11.9 ± 3.0 vs. 9.5 ± 1.8, P < 0.001) and the global circumferential strain (GCS) absolute value (19.0 ± 3.6 vs. 9.5 ± 1.8, P < 0.001) were significantly higher than in HCM patients. The native T1 (1334.9 ± 49.9 vs. 1318.2 ± 32.4 ms, P < 0.0001) and ECV values (37.8 ± 5.7 vs. 31.3 ± 2.5%, P < 0.0001) were higher than that of HCM patients. In multiparameter CMR models, GCS (2.097, 95% CI: 1.292–3.403, P = 0.003), GLS (1.468, 95% CI: 1.078–1.998, P = 0.015), and ECV (0.727, 95% CI: 0.569–0.929, P = 0.011) were the significant variables for the discrimination of the early-stage AL CA patients from HCM patients. ROC curve analysis and Youden’s test were used on GCS, GLS, ECV, and pairwise parameters for differentiating between Mayo stage I/II AL CA and HCM patients, respectively. The combination of GLS, GCS, and ECV mapping could distinguish Mayo stage I/II AL amyloidosis patients from hypertrophic cardiomyopathy with excellent performance (AUC = 0.969, Youden index = 0.813). Conclusion In early-stage AL CA patients with atypical LGE, who had similar imaging features as HCM patients, ECV mapping, GCS, and GLS were correlated with the clinical classification of the patients. The combination of GCS, GLS, and ECV could differentiate early-stage AL CA from HCM patients. Multiparameter CMR has the potential to provide an effective and quantitative tool for the early diagnosis of myocardial amyloidosis.